Rare Presentation of Breast Cancer - Figueiredo,Luísa Martins (2019)
Breast cancer is the most common tumour in women. Only 5-15% of breast cancer patients have distant metastases at diagnosis. Here we describe the case of a previously healthy 43-year-old woman with nausea, postprandial epigastric pain, and constipation as the first clinical presentation of breast cancer. Total colonoscopy revealed colon metastases and the immunohistochemical profile favoured primitive invasive lobular carcinoma of the breast. Gastrointestinal tract metastases are more frequent in lobular histology of breast cancer. Stomach and small intestine are the most common metastatic sites, while colon metastases are a rare occurrence.